OS CAMINHOS DA MULHER LÉSBICA: UMA ANÁLISE DO ROMANCE TOQUE DE VELUDO, DE SARAH WATERS - Veiga Castello Branco, Letícia (Inventário, 2024)
In Sarah Waters’ book, Tipping the Velvet, the author tells the story of Nancy Astley during a process of self-discovery as a lesbian woman. Using a Neo-victorian narrative, her character searches to overcome a betrayal and to deal with her homosexual sexuality she has found in herself publicly. The city of London serves as the backdrop for Nancy’s movements, reinforcing her need to exist, while also reflecting the protagonist’s perspective on society and her own thoughts and discussions regarding the recognition of her identity in association with her choices in the narrative. This article will explore the relationship between Nancy and different parts of London, examining how the city’s influence is able to shape the character’s emotions, in connection with her own sexuality as a lesbian woman. Additionally, it will present the novel of formation as representative of the character’s choices, who finds herself entangled in the past but also aims to move forward.